Threatened fishes of the world: Alburnoides petrubanarescui Bogutskaya & Coad 2009 (Actinopterygii: Leuciscidae) - Arash Jouladeh-Roudbar; Saber Vatandoust (Caspian Journal of Environmental Sciences)
Alburnoides petrubanarescui is endemic to the Urmia Lake basin, shared by Iran and Turkey. Previously, the species was found in several rivers in this basin, however, it is currently only found in the upper part of the Nazlu Chay River. The species' extent of occurrence (EOO), which was previously estimated to be 20.000 km2, is now 300 km2. Over the past three generations (10 years), the EOO of Urmia spirlin has decreased by 98%, however, the population of the Nazlu River is stable, and there is no strong evidence to suggest that the population will decline in the future. Drought and water abstraction cause the species' population to reduce. Dam building and river pollution reduce their range, making them vulnerable to extinction. Therefore, we classified the species as Vulnerable D2.